Measured and perceived indices of fluid balance in professional athletes. The use and impact of hydration assessment strategies. Issue 3 (16th March 2018) - Love, T.D.; Baker, D.F.; Healey, P.; Black, K.E.
ABSTRACT: Background : To determine athletes perceived and measured indices of fluid balance during training and the influence of hydration strategy use on these parameters. Methods : Thirty-three professional rugby union players completed a 120 minute training session in hot conditions (35°C, 40% relative humidity). Pre-training hydration status, sweat loss, fluid intake and changes in body mass (BM) were obtained. The use of hydration assessment techniques and players perceptions of fluid intake and sweat loss were obtained via a questionnaire. Results : The majority of players (78%) used urine colour to determine pre-training hydration status but the use of hydration assessment techniques did not influence pre-training hydration status (1.025 ± 0.005 vs. 1.023 ± 0.013 g . ml −1, P  = .811). Players underestimated sweat loss (73 ± 17%) to a greater extent than fluid intake (37 ± 28%) which resulted in players perceiving they were in positive fluid balance (0.5 ± 0.8% BM) rather than the measured negative fluid balance (−1.0 ± 0.7% BM). Forty-eight percent of players used hydration monitoring strategies during exercise but no player used changes in BM to help guide fluid replacement. Conclusion : Players have difficulty perceiving fluid intake and sweat loss during training. However, the use of hydration monitoring techniques did not affect fluid balance before or during training.